2022
DOI: 10.3390/cells11030349
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell–Tumor Interactions: Molecular Mechanisms of Recruitment, Intratumoral Communication and Potential Therapeutic Targets for Tumor Growth

Abstract: Mast cells (MCs) are tissue-resident immune cells that are important players in diseases associated with chronic inflammation such as cancer. Since MCs can infiltrate solid tumors and promote or limit tumor growth, a possible polarization of MCs to pro-tumoral or anti-tumoral phenotypes has been proposed and remains as a challenging research field. Here, we review the recent evidence regarding the complex relationship between MCs and tumor cells. In particular, we consider: (1) the multifaceted role of MCs on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 273 publications
(287 reference statements)
0
30
0
Order By: Relevance
“…Possible explanations for this phenomenon include the potential influence of specific TMEs on MC phenotype, which could lead MCs to synthesize particular mediators able to favor or limit tumor cell replication, blood vessel formation, or intratumoral immune response. To date, the mediators and conditions modulating MC activation in particular TMEs have not been fully described, and potential phenotypic changes on tumor-associated MCs (TAMCs) are largely unknown [ 13 , 21 , 22 ], although TAMCs seem to constitute a particular subpopulation of MCs that are different to the classical categories that have been used to date [ 59 ]. From all the factors present in the TME that activate MCs and can modify their phenotype (such as stem cell factor, adenosine, and IL-33, among others), cyH is one of the least studied.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Possible explanations for this phenomenon include the potential influence of specific TMEs on MC phenotype, which could lead MCs to synthesize particular mediators able to favor or limit tumor cell replication, blood vessel formation, or intratumoral immune response. To date, the mediators and conditions modulating MC activation in particular TMEs have not been fully described, and potential phenotypic changes on tumor-associated MCs (TAMCs) are largely unknown [ 13 , 21 , 22 ], although TAMCs seem to constitute a particular subpopulation of MCs that are different to the classical categories that have been used to date [ 59 ]. From all the factors present in the TME that activate MCs and can modify their phenotype (such as stem cell factor, adenosine, and IL-33, among others), cyH is one of the least studied.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study demonstrated that MCs exposed to chH (24 h at 1% O 2 ) increased the secretion of the chemokine CCL-2, and this secretion was dependent on ROS formation and the translocation of L-type Ca 2+ channels to the plasma membrane [ 28 ]. Interestingly, hypoxic MCs also promoted the translocation of lysosome-associated membrane protein 2 (LAMP2)-positive vesicles from intracellular pools to the plasma membrane [ 13 ]. LAMP translocation has been associated with the activation of MCs and basophils [ 79 ], since it can be related to the mobilization of granules to the plasma membrane and, eventually, to an increase in MCs degranulation [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations